Regularization methods for the construction of preconditioners for saddle point problems - Axelsson, Owe (Proceedings of the Conference Algoritmy, 2020)
For the iterative solution of saddle point problems one needs efficient preconditioners to achieve a fast convergence. Three types of preconditioners are presented which are based on regularization by use of an augmented matrix. They are applicable also for problems with a highly singular pivot block matrix. One of the methods is applicable also for nonsymmetric saddle point problems.